Respuesta :
Answer:
The speed of the spider is v = (2g*L*(1-cosθ))^1/2
Explanation:
using the energy conservation equation we have to:
Ek1 + Ep1 = Ek2 + Ep2
where
Ek1 = kinetic energy = 0
Ep1 = potential energy = m*g*L*cosθ
Ek2 = (m*v^2)/2
Ep2 = m*g*L
Replacing, we have:
0 - m*g*L*cosθ = (m*v^2)/2 - m*g*L
(m*v^2)/2 = m*g*L*(1-cosθ)
v^2 = 2g*L*(1-cosθ)
v = (2g*L*(1-cosθ))^1/2
The speed of the spider is [tex]v =\sqrt{2g*L*(1-cos\theta)}[/tex]
Energy conservation:
Energy can neither be created nor destroyed; rather, it can only be transformed or transferred from one form to another.
From the energy conservation equation we have to:
Ek1 + Ep1 = Ek2 + Ep2
where
Ek1 = kinetic energy = 0
Ep1 = potential energy = m*g*L*cosθ
Ek2 = (m*v²)/2
Ep2 = m*g*L
On substituting the values:
[tex]0 - m*g*L*cos\theta = (m*v^2)/2 - m*g*L\\\\(m*v^2)/2 = m*g*L*(1-cos\theta)\\\\v^2 = 2g*L*(1-cos\theta)\\\\v = \sqrt{(2g*L*(1-cos\theta))}[/tex]
Find more information about Energy conservation here:
brainly.com/question/12306849